The effects of temperature on Bosmina longirostris susceptibility to microcystin-LR acute toxicity - Lamb, Madison C.; Kimmel, David G.; Field, Erin K. (My University, 2019)
Harmful algal blooms are an ongoing threat to many aquatic systems throughout the world. In the Chowan River, North Carolina, the frequency of toxin producing Microcystis aeruginosa blooms has increased since 1975 along with an average 0.71°C rise in water temperature. The combined effect of microcystin-LR toxin and rising temperatures on a dominant zooplankter in the system, Bosmina longirostris, was the focus of this study. Laboratory studies were conducted to determine how microcystin-LR, produced from M. aeruginosa blooms, affected B. longirostris mortality under different temperature regimes. At 25°C, the LC50 for B. longirostris was 26.3 μg L-1 suggesting that B. longirostris can survive typical current bloom microcystin-LR concentrations ranging 0.1μg L-1 to 2.0 μg L-1, but would be susceptible to higher concentrations they may be periodically exposed to. Mortality was assessed at a constant microcystin-LR concentration of 26.3 μg L-1 over 15–35°C, and it was found that B. longirostris mortality increased at higher temperatures. B. longirostris mortality increased approximately 18% due to microcystin-LR alone over 2°C between 25°C and 27°C when exposed to the LC50 concentration. The increased prevalence of toxic M. aeruginosa blooms and increasing temperatures due to climate change may reduce B. longirostris populations, potentially affecting larval fish and fisheries in the Chowan River, North Carolina.
Keywords: Toxins; Toxicity; Zooplankton; Algae; Death rates; Surface water; Copepods; Daphnia